1976
DOI: 10.1017/s0021859600061013
|View full text |Cite
|
Sign up to set email alerts
|

The body composition of growing sheep during milk feeding, and the effect on composition of weaning at various body weights

Abstract: Thirty-four (13 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

1979
1979
1997
1997

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…In this study, development of adipose tissues, expressed both in absolute terms and relative to empty LW, was greater between 24 and 36 kg LW than between 12 2 and 24 kg. This is consistent with the observation that adipose tissue is the tissue which develops the latest and its allometric coefficient is between 1.3 and 1.6 (Hammond, 1932;Fourie et al, 1970;Kirton et al, 1972; Kempster, 1980 (Searle and Griffiths, 1976 (1985) founding that in kids the largest relative weight lost after weaning among the depots studied omental, mesenteric, perirenal and pericardic was observed in the perirenal depot.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, development of adipose tissues, expressed both in absolute terms and relative to empty LW, was greater between 24 and 36 kg LW than between 12 2 and 24 kg. This is consistent with the observation that adipose tissue is the tissue which develops the latest and its allometric coefficient is between 1.3 and 1.6 (Hammond, 1932;Fourie et al, 1970;Kirton et al, 1972; Kempster, 1980 (Searle and Griffiths, 1976 (1985) founding that in kids the largest relative weight lost after weaning among the depots studied omental, mesenteric, perirenal and pericardic was observed in the perirenal depot.…”
Section: Discussionsupporting
confidence: 84%
“…Although previous work has shown similar changes in composition (Mitchell & Jagusch 1972;Penning & Treacher 1975;Searle & Griffiths 1976), it has also been suggested that early nutritional effects on composition tend to be less pronounced at live weights above 40 kg. The results show that extreme weaning-age treatments markedly affected growth performance, but at the same time achieved differences in carcass composition over the 30-50 kg liveweight range.…”
Section: Discussionmentioning
confidence: 91%
“…given milk-substitutes varying in crude protein (nitrogen x 6.25) content from 120 to 460 g/kg, while Searle and colleagues studied the changes in the body composition of lambs whilst with their mothers at pasture, or when given a cow's-milk diet and weaned under pen conditions (Searle, 1970;Searle et al 1972;Searle & Griffiths, 1976). These authors are agreed that when lambs are restricted to a particular diet, such as reconstituted cow's milk, their body composition is closely related to body-weight rather than to age or rate of gain, an observation which is in agreement with the conclusions of Mitchell et al (1928).…”
mentioning
confidence: 99%